PENERAPAN MEDIA GRAFIS DALAM MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM (MIN Sungai Cabang Barat Sukamara) - Zaenuddin, Muhammad (LP2M IAIN Palangka Raya, 2014)
This study focuses on graphic media to explain subjects SKI focusing first issue any graphic media used by teachers in the subjects in class VI MIN SKI Sungai Cabang Barat; secondly whether the message content has a graphics media contain elements of organizing visual message content properly; The third is the message content may facilitate the understanding of the graphic media coverage students understand the lesson content. This study aims to determine the graphic media teachers can use in class VI SKI MIN Sungai Cabang Barat, and the content of the message the media has an element of media in organizing the visual content of the message well and know the contents of the message easier to understand the subject matter coverage.After doing research on the application of the graphic media the results are as follows: first, teachers use graphic media SKI is adapted from the material presented and the subject teachers ability to implement such a process chart, charts, descriptions, and images / photos. The second message SKI graphic media in learning is not fully contained graphic elements in the use of visual messages properly. The third the content of the message in the graphic media SKI learning it can facilitate students in understanding the scope, the content and subject matter provided it is justified by the students of class VI MIN Sungai Cabang Barat